2010
DOI: 10.1002/bbb.245
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of selected future energy crops for Europe

Abstract: Life cycle assessment (LCA) methodology is increasingly used to determine the potential environmental impacts of biofuels and bioenergy. This paper presents the outcomes of screening LCAs of 13 future energy crops for Europe summarizing the results of the EC-funded project 4F CROPS -Future Crops for Food, Feed, Fiber and Fuel. For analysis, these dedicated energy crops -representing seven environmental zones in Europe -are combined with a multitude of processing and utilization options, resulting in 120 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…Higher yields are reported for dedicated species for biomass production, such as the woody willow (8.2-15.0 Mg DM ha -1 ), poplar (10.7-15.0 Mg DM ha -1 ), eucalyptus (15.0-20.0 Mg DM ha -1 ) (Venendaal et al, 1997;Kauter et al, 2003;Rettenmaier et al, 2010;Cosentino et al, 2012c), or the herbaceous perennial switchgrass (5.0-20.0 Mg DM ha -1 ) (Elbersen et al, 2013;.…”
Section: Articlementioning
confidence: 95%
See 1 more Smart Citation
“…Higher yields are reported for dedicated species for biomass production, such as the woody willow (8.2-15.0 Mg DM ha -1 ), poplar (10.7-15.0 Mg DM ha -1 ), eucalyptus (15.0-20.0 Mg DM ha -1 ) (Venendaal et al, 1997;Kauter et al, 2003;Rettenmaier et al, 2010;Cosentino et al, 2012c), or the herbaceous perennial switchgrass (5.0-20.0 Mg DM ha -1 ) (Elbersen et al, 2013;.…”
Section: Articlementioning
confidence: 95%
“…It has been reported that perennial herbaceous crops have the potential to reduce the disadvantage associated with the change in land use (e.g. due to their potential introduction in marginal lands), competition of food vs fuels and in general environmental threats as compared to annual crops (Fernando et al, 2010;Rettenmaier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Energy savings, greenhouse eff ects, and acidifi cation issues are being dealt in Rettenmaier et al 17 environmental performance and the liabilities of dedicated crops. [2][3][4][5][6] Most energy crop systems require intensive use of land.…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%
“…The whole life cycle of the products: the cultivation of the plants, production and transportation, the utilization, and the disposal, has to be assessed. Several factors may affect the amount of fossil energy sources replaced/conserved, such as the crop management and biomass yield (which is highly dependent on geographical location), the conversion technologies and its use for bioenergy, biofuels or bioproducts (Biewinga and van der Bijl 1996;Rettenmaier et al 2010b).…”
Section: Replacement/conservation Of Fossil Energy Sourcesmentioning
confidence: 99%